Optimization of waste collection and disposal in Kampala city. (October 2015) - Kinobe, J.R.; Bosona, T.; Gebresenbet, G.; Niwagaba, C.B.; Vinnerås, B.
Abstract: Waste collection and transportation is an important municipal service that involves high expenditures if not handled efficiently. This has hindered waste management in many Sub-Saharan African countries. In this study, Geographic Information System (GIS) tools were used to optimize travel distances, trips and collection time, which leads to maximizing total waste collection, yielding large savings and keeping the environment clean. The study suggested the best waste collection routes, and determined a suitable vehicle fleet and capacity to be used by Kampala Capital City Authority (KCCA), which is the body responsible for waste management in Kampala. The use of the GIS tools led to the reduction in the total number of trips and travel distances, which decreased fuel consumption and vehicle emissions. In addition, the model can be used by the various outsourced private operators, collecting and disposing of solid wastes. Since the current municipal landfill for Kampala city is almost full, the GIS tool was used to identify the optimum location of a new proposed landfill site, based on optimized travel distances. The results of this study can help KCCA to decrease costs of managing wastes and environmental as well as social impacts. Highlights: The study uses GIS to optimize travel distances, trips and collection time of waste. The study suggest the best waste collection routes, suitable vehicle fleet number and capacity. Optimal facility location of a new proposed waste landfill is identified with regard to travel distances. Fuel costs are reduced and consequently reducing on the greenhouse gas emissions. Study minimizes on waste collection costs and keeps the environment clean.